Keberadaan Perempuan di Ruang Publik (Analisis Hadis Perspektif Heremenutika Yusuf Al-Qardhawi) - Moh Paris Fauzi Sawedi; Nur Hidayat; Nada Nabilah Syafiqoh (AL QUDS : Jurnal Studi Alquran dan Hadis, 2022)
Presence of Women in Public Space(Analysis of Hadith from Yusuf Al-Qardhawi's Hermeneutical Perspective)This study aims to analyze the hadith about women being in public spaces. This research is a library research with a descriptive qualitative approach and Yusuf Qardhawi's hermeneutics is the theory used to analyze the data. The results of this study indicate that the position of women and men in the public sphere is the same, that is, both women and men have the right to be elected and to vote because women are beings who receive Shari'a orders as men in general are ordered to worship Allah, uphold their religion, carry out what is obligatory and leave what is unlawful, invite people to goodness and prevent people from heinous and evil deeds. Women are allowed to lead if they lead women as well as in women-only communities. It is permissible for women to become leaders in the public space, and that does not conflict with social interests.